Effectiveness Analysis of the Utilization Liquid Smoke Distilled from Organic Materials as an Alternative for Fish Preservation - Candra Dewi; Sulhadi Sulhadi; T. Darsono; E. D. Pratiwi (Journal of Natural Sciences and Mathematics Research, 2019)
Liquid smoke is alternative preservation fish that does not cause pollution and does not damage the respiratory organs. Liquid smoke contains antibacterial and antioxidant so that it can preserve fish that have a fast rot character. This study aims to determine the characteristics and effectiveness of using liquid smoke as an alternative to preserving fish. The research method applied in preserving fish using liquid smoke is soaked; soaked and dried; and soaked and aerated. The variables in this study include the combination of bay leaves, lemongrass, and galangal; Pandan leaves; and tuna. The results showed that the characteristics of the liquid smoke of bay leaves, lemongrass and galangal and pandan leaves were almost the same clear color, the level of viscosity was like water, and the smell of smoke flavor each stung the distinctive aroma of organic matter. Based on data analysis, it was found that an effective way to use liquid smoke in replacing traditional fumigation was to soak it than dried in the sun. This is because soaking can increase antibacterial activity while drying can reduce water content in fish.©2019 JNSMR UIN Walisongo. All rights reserved.